ENVIRONMENTAL SANITATION: STRATEGIES AND CHALLENGES IN WASTE MANAGEMENT - Budi Susetyo (Adisam Publisher, 2024)
Waste management is one of today's most crucial environmental challenges that demands innovative and integrative solutions. The study conducted in this research uses the literature research method. The results show that the effectiveness of waste management depends not only on the application of green technology and adequate infrastructure but also on active participation and public awareness of sanitation issues. The implication of this study suggests the importance of a holistic approach to waste management, which includes a combination of technological innovation, supportive regulations, public education, and the involvement of all stakeholders.